2021
DOI: 10.1039/d1cp00865j
|View full text |Cite
|
Sign up to set email alerts
|

HCl–H2O dimer: an accurate full-dimensional potential energy surface and fully coupled quantum calculations of intra- and intermolecular vibrational states and frequency shifts

Abstract: The interaction between HCl and H2O is of considerable theoretical and experimental interest due to its important role in atmospheric chemistry and understanding the onset of the dissociation of HCl...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 60 publications
3
71
0
Order By: Relevance
“…One of the two symmetrically equivalent nonplanar minimum-energy structures of the HCl–H 2 O dimer on PES-2021, from ref . The distances are in ångstrom, and angles are in deg.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the two symmetrically equivalent nonplanar minimum-energy structures of the HCl–H 2 O dimer on PES-2021, from ref . The distances are in ångstrom, and angles are in deg.…”
Section: Introductionmentioning
confidence: 99%
“…This major gap was finally filled by our recent theoretical study reported in ref , denoted hereafter as paper I. Its aims were twofold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex (HCl) [44][45][46] Fourier transform infrared (FTIR) spectroscopy in supersonic jets, 47,48 inert matrices [49][50][51][52][53][54] and Helium nanodroplets, [55][56][57] time-of-flight mass spectrometry and velocity-map imaging used to observe vibrational predissociation of the complex 58,59 and infrared cavity ringdown spectroscopy. 60,61 Many theoretical analyses using ab initio electronic structure methods [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] were published as well.…”
Section: Introductionmentioning
confidence: 99%
“… 23 Jiang et al 24 proposed a rigorous, accurate, and efficient permutation invariant polynomial‐neural network approach (PIP‐NN) to fit the PESs of gas‐surface systems, In PIP‐NN, symmetries are enforced by symmetrized monomial inputs of neural networks. It has been successfully used to construct accurate PESs for Ne‐C 2 H 2 , H 2 O‐CO, HCl‐H 2 O, 25–28 and so on.…”
Section: Introductionmentioning
confidence: 99%